Training Needs of Teachers and Implementation of a Model for Their Determination - Lidia Lara Díaz; Mayté Benítez Rodríguez; Coralia Juana Pérez Maya; Luís Rafael Sánchez Arce; Ania Carballosa González (Medisur)
Background: in the study of training process, which will consider factors related to new knowledge, it is necessary to identify the needs that justify it. Objective: to discuss the methodology used to determine training needs of university teachers based on the implementation of a deductive model, which was illustrated in a teacher-training program. Methods: document analysis was conducted to examine the contents of the thesis paper; the use of inductive-deductive and analytic-synthetic methods was also emphasized. Results: the coherent and consistent application of the steps of the David Leyva’s deductive model in the different stages of the research process is described. Conclusions: the methodology used is suitable for determining training needs of research tutors and allowed solving the research problem.